Airborne Laser Communication System with Automated Tracking - Xizheng Ke; Hanli Liang (International Journal of Optics)
The acquisition, alignment, and tracking system is an important part of airborne laser communication and is the prerequisite and guarantee for the normal communication link. In order to solve the problem of automatic tracking of laser communication links in the airborne environment, the rapid capture, alignment, and tracking of beams between terminals are realized. This article proposes a stepping motor as a control servo system and a four-quadrant detector as an automatic tracking method for the detection unit. The pulse width modulation signal controls the rotation speed of the stepping motor and combines the position distribution of the light spot on the four-quadrant detector to achieve high-precision beam tracking. On this basis, indoor simulation experiments are carried out. After many experiments, the tracking accuracy is better than 2.5 μrad, which shows that the system can be applied to airborne laser communication, and it is verified that this method has good automatic tracking performance for airborne laser communication.